The Oxford Needle Experience (ONE) scale: a UK-based and US-based online mixed-methods psychometric development and validation study of an instrument to assess needle fear, attitudes and expectations in the general public - Kantor, J; Vanderslott, S; Morrison, M; Pollard, AJ; Carlisle, RC (BMJ Publishing Group, 2023)
Objectives: To develop and validate the Oxford Needle Experience (ONE) scale, an instrument to assess needle fear, attitudes and expectations in the general population. Design: Cross-sectional validation study. Setting: Internet-based with participants in the UK and USA. Participants: UK and US representative samples stratified by age, sex, and ethnicity using the Prolific Academic platform. Main outcome measures: Exploratory factor analysis with categorical variables and a polychoric correlation matrix followed by promax oblique rotation on the UK sample for the ONE scale. Confirmatory factor analysis (CFA) with a Satorra-Bentler scaled test statistic evaluating the root mean squared error of approximation (RMSEA), standardised root mean squared residual (SRMR) and comparative fit index (CFI) on the US sample. Reliability as internal consistency using McDonald’s omega. Convergent validity using the Pearson correlation coefficient. Predictive and discriminant validity using logistic regression ORs of association (OR). Results: The population included 1000 respondents, 500 in the UK and 500 in the USA. Minimum average partial correlation and a scree plot suggested four factors should be retained: injection hesitancy, blood-related hesitancy, recalled negative experiences and perceived benefits, yielding a 19-question scale. On CFA, the RMSEA was 0.070 (90% CI, 0.064 to 0.077), SRMR 0.053 and CFI 0.925. McDonald’s omega was 0.92 and 0.93 in the UK and US samples, respectively. Convergent validity with the four-item Oxford Coronavirus Explanations, Attitudes and Narratives Survey (OCEANS) needle fear scale demonstrated a strong correlation (r=0.83). Predictive validity with a single-question COVID-19 vaccination status question demonstrated a strong association, OR (95% CI) 0.97 (0.96 to 0.98), p<0.0001 in the US sample. Discriminant validity with a question regarding the importance of controlling what enters the body confirmed the ONE score does not predict this unrelated outcome, OR 1.00 (0.99, 1.01), p=0.996 in the US sample. Conclusions: The ONE scale is a reliable and valid multidimensional scale that may be useful in predicting vaccine hesitancy, designing public health interventions to improve vaccine uptake and exploring alternatives to needles for medical procedures.